Vaginal flora during pregnancy and subsequent risk of preterm birth or prelabor rupture of membranes: a nested case-control study from China - Xiaomei Liu; Shuting Si; Li Huang; Meiliang Zhang; Wenya Chen; Liquan Wang; Yunxian Yu (BMC, 2023)
Abstract Background The findings of the association of vaginal flora with preterm birth (PTB) or prelabor rupture of membranes (PROM) were conflicts. Moreover, vaginal flora was different by ethnicity and the evidence from China was limited. Methods This study was a nested case control study, based on Yiwu birth cohort. We assessed vaginal microbiota in the second or third trimester, using 16S rDNA Amplicon Sequencing and explored the association between the diversity and composition of vaginal flora and PTB or PROM. Results We finally included 144 pregnant women. In present study, the alpha diversity of TPROM (Term prelabor rupture of membranes) samples was lower than that of full term samples (Chao1 index: P < 0.05). When we further categorized PTB (Preterm birth) into SPB (PTB without PROM) and PPROM (Preterm prelabor rupture of membranes), there was no difference between SPB and full term. In addition, we found that the proportion of PCoA2 in TPROM group was different from that in full term group and preterm group. The difference between groups was significant according to anosim analysis (R = 0.059, P < 0.001). With LEfSe (Linear discriminant analysis Effect Size) analysis, we found that the abundance of Lactobacillus in the vaginal flora of pregnant women with preterm birth was the highest (P = 0.003). Conclusion In Chinese pregnant women, the alpha diversity in TPROM group was significantly lower than that in both PTB and full term group. However, there was no difference between PTB and full term. Lactobacillus was the most abundant in preterm birth group. More studies should be conducted to confirm our findings.